Technological advancements, digital transformation, and future trends in blood transfusion services - Varghese, Abin; Thilak, Kavitha; Thomas, Saritha Mary (International Journal of Advances in Medicine, 2024)
Misidentification, mistransfusion, and pre-analytical errors are all regarded as major challenges and risks in safe blood transfusion procedures. To provide a high level of accuracy, traceability, automation, and reliability in blood transfusion services, traditional methods should be upgraded with modern technologies such as block chain technology, machine learning, artificial intelligence (AI), artificial neural networks, algorithm-based learning, and the implementation of radio frequency identification (RFID) and the internet of things (IoT). This technology helps reduce errors, retrieve data, forecast blood demand, reduce blood waste, manage blood storage, and manage workload, ensuring transfusion safety. The technology is still in the initial stages of development and by addressing issues such as data loss, patient data privacy, and cost-effectiveness, the technology will become a revolution in transfusion services.